Police leadership in developing youth leaders in the community: positive youth development perspectives in Malaysia - Arshad, Mohd Mursyid; Tan, Hua Hong (Human Resource Management Academic Research Society, 2019)
Youth leadership development is one of the important agenda needed in the country's development agenda as outlined in the Malaysian Youth Policy 2015. The involvement of young leaders can be strengthened through wider exposure and professional training that enhances Positive Youth Development among youths. Thus, in community context, the role of police leadership is not merely just as law enforcement officer but an icon of leadership. The authority in public order and security granted by the law to the police officer can be a positive exertion to influence the youth and it has the potential in providing that kind of learning process. Therefore, this paper will explore the process of youth development towards PYD and how police leadership enhanced youth to become leader in the community. The discussion addressed in this paper is how police leadership contributes to the process of developing youth leadership ability form at risk behavior and eventually fulfilling the overall PYD needs.